The Irish Polka - Hall, S. C., Mrs., 1800-1881 (1840)
Figure of a man dancing a polka.
Title inscribed on backing sheet.
Attributed to unidentified artist.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43.
Keywords: Dancers -- Ireland -- 1830-1840; Ink drawings -- Irish -- 1830-1840.